Chronic heat stress alters hypothalamus integrity, the serum indexes and attenuates expressions of hypothalamic appetite genes in broilers. (April 2019) - He, Xiaofang; Lu, Zhuang; Ma, Bingbing; Zhang, Lin; Li, Jiaolong; Jiang, Yun; Zhou, Guanghong; Gao, Feng
Abstract: The hypothalamus is crucial to ensure the functionality of the entire organisms, such as body temperature, feed intake and energy regulation. Exposing broilers to high ambient temperature usually induces lower feed intake and energy imbalance. We investigated the molecular mechanisms by which heat stress impairs the appetite via dysfunction in hypothalamus of the broilers. Broilers were allocated to three groups: the normal control (NC) group, and fed ad libitum; heat-stress (HS) group, and fed ad libitum; pair-fed (PF) group, which received the feed intake equal to HS group. Experiment lasted from the age of 28 to 42 d. The results showed that HS increased the head surface temperature of broiler and changed hypothalamic ultrastructure. HS treatment also increased the serum corticosterone in the broilers after 7 days of heat stress, elevated the FT4 and FT3 after 14 days of heat stress. Heat stress of 14 days showed a tendency to increase the leptin. However, the serum corticosterone in the HS group had no significant difference after 14 days of heat stress. In addition, HS treatment decreased the expression of orexigenic gene neuropeptide Y (NPY) after 14 days of heat stress, while HS treatment had no effect on the reactive oxygen species (ROS), as well as the gene expression of AMPKα1 and LKB1 in the hypothalamus. In conclusion, HS increased the surface temperature of head in broiler, and then altered the integrity of hypothalamus. Meanwhile, HS increased the serum corticosterone which may ascribe to the activation of HPA axis in the broilers. In addition, chronic heat stress decreased the expression of orexigenic gene NPY, which may cause the broiler to reduce feed intake. Highlights: The study was aim to estimate effects of heat stress on head surface temperature, appetite-related genes in the broilers. Chronic heat stress increased the broilers' head temperature and changed hypothalamus integrity. Chronic heat stress increased the serum corticosterone. Chronic heat stress upregulated the mRNA and protein expression of neuropeptide Y in the hypothalamus.